Zany wooden toys reloaded! : more wild projects from the toy inventor's workshop - Gilsdorf, Bob, 1963- (Fox Chapel Publishing, 2013)
"Your mission is to invent, build and control wild and wacky toys! Are you up for the challenge? This madcap follow-up to Zany Wooden Toys that Whiz, Spin, Pop, and Fly is sure to thrill the ten-year-old creator in your life. Zany Wooden Toys Reloaded! is packed with author Bob Gilsdorf's best and most creative projects. Disarm spy robots, launch flying discs, throw cards magically across the room--each of these imaginative woodworking projects ranks high on the fun scale! Inside you'll find 8 show-stopping creations that will delight kids and adults alike: -Magician's Envy Cardthrower -Boomerang Launcher -Bottle Cap Shooter -Pirate Coin Maker -Crayon Dispenser -Desktop Flicker-er -Knobby Knocker -Energy Orb Robot Battle -Gumball Smackdown "--